Applied formal verification. - Perry, Douglas L., ....-; Foster, Harry D., 1956- (New York : McGraw-Hill, 2005)
PREFACE Chapter 1: Introduction to Verification Chapter 2: Verification Process Chapter 3: Current Verification Techniques Chapter 4: Introduction to Formal Techniques Chapter 5: Formal Basics and Definitions Chapter 6: Property Specification Chapter 7: The Formal Test Plan Process Chapter 8: Techniques for Proving Properties Chapter 9: Final System Simulation APPENDIX A: IEEE 1850 PSL PROPERTY SPECIFICATION LANGUAGE APPENDIX B: IEEE 1800 SYSTEM VERILOG ASSERTIONS BIBLIOGRAPHY INDEX
Keywords: Digitale elektronica; Geïntegreerde schakelingen; Logische schakelingen